The Implementation of Micro and Small Business Licensing Policy Based on the Online Single Submission (OSS) in Cirebon City - Nabila, Syalma Ghusti; Putri, Meyrani Anggita; Siswoyo, Mukarto; Imawan, Khaerudin (Indonesian Journal of Advanced Research, 2025)
This study analyzes the implementation of the Online Single Submission (OSS) system for Micro and Small Business Licensing (UMK) in Cirebon City, using George C. Edward III’s framework of communication, resources, disposition, and bureaucratic structure. The OSS system, mandated by Government Regulation No. 5 of 2021, aims to simplify the process of obtaining a Business Identification Number (NIB) for UMK actors. Using a descriptive qualitative approach, data were collected through interviews, observations, documentation, and triangulation involving DPMPTSP officers and business actors. The findings reveal that while resources and staff commitment are adequate, challenges persist in communication, incentive provision, and fragmented inter-agency SOPs. To enhance implementation effectiveness, the study recommends improved outreach, better coordination among agencies, and the provision of appropriate incentives.